2016
DOI: 10.1016/j.chiabu.2016.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Children exposed to intimate partner violence: Identifying differential effects of family environment on children's trauma and psychopathology symptoms through regression mixture models

Abstract: The majority of analytic approaches aimed at understanding the influence of environmental context on children’s socioemotional adjustment assume comparable effects of contextual risk and protective factors for all children. Using self-reported data from 289 maternal caregiver-child dyads, we examined the degree to which there are differential effects of severity of intimate partner violence (IPV) exposure, yearly household income, and number of children in the family on posttraumatic stress symptoms (PTS) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 52 publications
2
18
0
6
Order By: Relevance
“…The institutional review board at the University of Denver approved these procedures. Further details on sample recruitment and participant characteristics can be found in the work of McDonald et al, .…”
Section: Methodsmentioning
confidence: 99%
“…The institutional review board at the University of Denver approved these procedures. Further details on sample recruitment and participant characteristics can be found in the work of McDonald et al, .…”
Section: Methodsmentioning
confidence: 99%
“…En las últimas dos décadas, un número creciente de estudios empíricos internacionales se centró en las experiencias de violencia de pareja entre adolescentes inmigrantes y étnicos que viven en América del Norte (adolescentes latinos, asiáticos y africanos) (Akers, Yonas, Burke, & Chang, 2011;McDonald et al, 2016;Lane & Gwartney-Gibbs, 1985;Malik, Sorenson, & Aneshensel, 1997;O'Keefe, 1997;Watson, Cascardi, Avery-Leaf, & O'Leary, 2001). Centrándonos en el caso de EE.UU, Giuliani (2017) sostiene que las encuestas nacionales en toda la escuela permitieron evaluar las tasas de prevalencia e incidencia de violencia en el noviazgo entre adolescentes que viven en los Estados Unidos, lo que confirma una mayor vulnerabilidad de los grupos étnicos minoritarios con respecto a las experiencias de victimización y perpetración de violencia en el noviazgo adolescente.…”
Section: La Pertenencia éTnica Y La Violencia En Parejas Adolescentesunclassified
“…These simulations included four different sample size conditions, from 200 as a small sample size condition, to 3,000 as a large sample size condition. Although previous simulation studies had shown that 3,000 is an adequate number for detecting the differential effect with a large effect size difference, many applied studies have employed the regression mixture approach with much smaller sample sizes (Dyer et al, 2012;McDonald et al, 2016;Wong, Owen, & Shea, 2012). Therefore, we included 200 as the smallest sample size condition in the present study.…”
Section: Data Generationmentioning
confidence: 99%
“…In another study, regression mixture approach was used to understand the differential effects of depressive symptoms and neuroticism on cognitive complaints in older adults (Kliegel & Zimprich, 2005). Given the exploratory nature of this approach, regression mixture models have become increasingly popular in the last decade (Dyer, Pleck, & McBride, 2012;Lanza, Cooper, & Bray, 2014;Lanza, Kugler, & Mathur, 2011;McDonald et al, 2016;Schmiege & Bryan, 2016;Silinskas et al, 2013;Silinskas et al, 2016).…”
mentioning
confidence: 99%